Serum homocysteine level is an independent risk factor for 1-year stroke recurrence in patients with acute ischemic stroke and H-type hypertension: results from the Xi'an stroke registry study of China - Zhang, Dandan; Liu, Zhongzhong; Guo, Weiyan; Lu, Qingli; Zhang, Huan; Lei, Zhen; Liu, Pei; Huang, Congli; Wang, Jing; Chang, Qiaoqiao; Lin, Xuemei; Wang, Fang; et al. (Frontiers in Neurology, 2023)
Background H-type hypertension has a high prevalence in China. However, the association of serum homocysteine levels with 1-year stroke recurrence in patients with acute ischemic stroke (AIS) and H-type hypertension has not been studied. Methods A prospective cohort study of patients with AIS admitted to hospitals between January and December 2015 in Xi'an, China, was conducted. Serum homocysteine levels, demographic data, and other relevant information were collected from all patients upon admission. Stroke recurrences were routinely tracked at 1, 3, 6, and 12 months after discharge. The blood homocysteine level was studied as a continuous variable and tertiles (T1–T3). A multivariable Cox proportional hazard model and a two-piecewise linear regression model were utilized to evaluate the association and ascertain the threshold effect regarding the serum homocysteine level and 1-year stroke recurrence in patients with AIS and H-type hypertension. Results Overall, 951 patients with AIS and H-type hypertension were enrolled, of whom 61.1% were male. After adjusting for confounders, patients in T3 had a significantly increased risk of recurrent stroke within 1 year, compared with those in T1 as the reference (hazard ratio = 2.24, 95% confidence interval: 1.01–4.97, p = 0.047). Curve fitting showed that serum homocysteine levels were positively curvilinearly correlated with 1-year stroke recurrence. Threshold effect analysis showed that an optimal threshold of serum homocysteine level <25 μmol/L was effective in reducing the risk of 1-year stroke recurrence in patients with AIS and H-type hypertension. Elevated homocysteine levels in patients with severe neurological deficits on admission significantly increased the risk of 1-year stroke recurrence (p for interaction = 0.041). Conclusions In patients with AIS and H-type hypertension, the serum homocysteine level was an independent risk factor for 1-year stroke recurrence. A serum homocysteine level of ≥25 μmol/L significantly increased the risk of 1-year stroke recurrence. These findings can inform the creation of a more precise homocysteine reference range for the prevention and treatment of 1-year stroke recurrence in patients with AIS and H-type hypertension and provide a theoretical foundation for the individualized prevention and treatment of stroke recurrence.